Pengaruh Faktor Iklim, ABJ Terhadap Kejadian Demam Berdarah Dengue Menggunakan Analisis Regresi - Lutfianawati, Ridha Fajar; marlik, Marlik; Ngadino, Ngadino; Nurmayanti, Demes; Sulistio, Irwan (UPPM Poltekkes Kemenkes Ternate, 2024)
Background: Dengue Hemorrhagic Fever or dengue is a health problem in Indonesia. Papar District of Kediri Regency is included in the area with the highest number of dengue cases. Purpose: knowing the climatic factors (rainfall, temperature, humidity) and ABJ that affect the incidence of DBD. Methods: This type of research is quantitative with retrospective methods. Research data is secondary data. The object of the study is climate factors, ABJ and dbd cases in 2016-2021 in Kediri Regency. Analyze data using linear regression. Results: The results of the correlation test are related between humidity, temperature, rainfall and ABJ with DBD, namely -0.273 (P = 0.029), 0.332 (P = 0.007), 0.286 (P = 0.022) and (P = 0.276). The form of regression equation is DBD = 78.1 + 0.01787 Rainfall + 0.986 Humidity with an R2 value of 22.53%. Conclusion: There is a significant relationship between DBD and Climate Factors (humidity, temperature, rainfall), there is no relationship of DBD with ABJ. Regression equations can be used to prepare for DHF prevention and control measures in the future.